Heat affected zone extension in pulsed Nd:YAG laser cutting of CFRP. (1st May 2018) - Leone, C.; Genna, S.
Abstract: Laser cutting is a promising alternative to the traditional methods in CFRP cutting. However, laser cutting is based on thermal interaction that results in thermal damages of both matrix and fibres. The heat affected zone (HAZ) extension is strictly dependent on the adopted laser source and the working parameters. The paper presents an experimental study on the laser cutting of CFRP plate, 1 mm in thickness by means of 150 W Nd:YAG pulsed laser. The cutting region and the influence of process parameters, pulse energy, pulse duration and overlapping, on the kerf geometry and the HAZ were analyzed. Experimental results showed that the adopted laser is able to cut the CFRP plate, up to 10.8 mm/s. However, an accurate selection of the process parameters is necessary in order to obtain the maximum cutting speed and a narrow HAZ. Moreover, a relation between the HAZ extension and the process parameters (average power, cutting speed, pulse frequency and pulse duration) was found.